PENGARUH WORD OF MOUTH DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA CAFE ALL IN ONE DI PANARUKAN - Wahyudi, Agus Tri; Praja, Yudha; Hamdun, Edy Kusnadi (Fakultas Ekonomi dan Bisnis, 2023)
In the era of globalization, business development is now increasing rapidly, one of which is the cafe business. The cafe business in Indonesia becomes one of the most promising businesses that is able to attract people's attention along with people's lifestyles, especially among teenagers and adults. This research aimed to find out the influence of word of mouth and service quality on repurchase intention through consumer satisfaction as an intervening variable at All In One cafe in Panarukan District. The population in this study was all consumers of All In One cafe. The sampling method used simple random sampling with a total of 98 consumers as respondents. The data analysis method applied Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of direct effect hypothesis test using Smart PLS 3.0 application indicated that word of mouth has a significant positive effect on consumer satisfaction, service quality has a significant positive effect on consumer satisfaction, word of mouth has a significant positive effect on repurchase intention, service quality has a positive but not significant effect on repurchase intention, consumer satisfaction has a positive but not significant effect on repurchase intention. The results of indirect effect hypothesis test showed that word of mouth does not significantly influence repurchase intention through consumer satisfaction, service quality does not significantly influence repurchase intention through consumer satisfaction.